A focus on quantitative methods to assess human factors in collaborative robotics - de Nobile, Alessia; Bibbo, Daniele; Russo, Marta; Conforto, Silvia (International journal of industrial ergonomics, 2024)
The advent of Industry 4.0 has transformed manufacturing by incorporating industrial robots to boost productivity and quality while cutting costs. Human-Robot Collaboration (HRC) is central to this shift, emphasizing seamless cooperation between humans and robots in shared workspaces. Evaluating the impact of such collaboration on human operators is crucial for efficiency, safety, and well-being. This systematic review explores methodologies for assessing human factors in HRC environments, spanning psychological, cognitive, and physical realms. Various evaluation methods have been identified, from subjective questionnaires to objective measurements. While subjective methods are the standard (especially questionnaires), there is a growing trend towards integrating physiological and physical measurements. The blend of subjective and objective methods offers a holistic understanding of human-robot interaction. This review adopts a more technical-oriented approach in the assessment of human factors in HRC. As a result, it consolidates existing methodologies and suggests avenues for further research, highlighting the significance of this assessment for enhancing productivity, safety, and well-being in industrial settings. •Industry 4.0 revolutionized manufacturing with robots to boost productivity, quality, and cost-efficiency, drivingHRC.•Evaluating the impact of HRC on human operators is essential for optimizing efficiency, safety, and well-being.•Various methods evaluate human factors in HRC, with questionnaires being the gold standard.•While subjective methods are prevalent, there is a growing trend to include objective measures of human factors in HRC.•Combining subjective questionnaires with objective measures offers a comprehensive view of HRC dynamics.